You are on page 1of 5

CHAPTER 5

SUMMARY
 If A(𝑋1 , 𝑌1 ) and B(𝑋2 , 𝑌2 ) are two distinct points.
𝑥 +𝑥 𝑦 +𝑦
(a) Midpoint of AB = ( 1 2 , 1 2)
2 2
𝑦2 −𝑦1 𝑦1 −𝑦2
(b) Gradient of AB = tan𝜃 = = , where 𝑥2 ≠ 𝑥1
𝑥2 −𝑥1 𝑥1 −𝑥2

 For two lines 𝑙1 and 𝑙2 ,

(a) 𝑙1 is parallel to 𝑙2 ⇔ the gradients are equal,
(b) 𝑙1 is perpendicular to 𝑙2 ⇔ the products of the gradients is -1,

 Equation of a straight line

(a) Equation of a line parallel to the x-axis, cutting the y-axis at (0, c) is
y=c
(b) Equation of a line parallel to the y-axis, cutting the x-axis at (a, 0) is
x=a
(c) Equation of a line passing through a given point (𝑥1 , 𝑦1 ) and having
gradient m is y - 𝑦1 = m(x - 𝑥1 )
EXAMPLE
1. The coordinates of 4 points are O(0, 0), A(2, k), B(2k, 9) and
C(3k, 2k + 7). Find the value(s) of k if
(a) The points O, A and B are collinear,
(b) OA is parallel to BC
Solution
(a) If O, A and B are collinear, they lie on the same straight line,
i.e. gradient of OA = gradient of OB
𝑘−0 9−0
=
2−0 2𝑘 − 0
𝑘 9
=
2 2𝑘
2𝑘 2 = 18
𝑘2 = 9
k = ±3
(b) OA is parallel to BC,
i.e. gradient of OA = gradient of BC.
𝑘−0 2𝑘 + 7 − 9
=
2−0 3𝑘 − 2𝑘
𝑘 2𝑘 − 2
=
2 𝑘
𝑘 2 = 4𝑘 − 4
(𝑘 − 2)2 = 0
𝑘=2

2. The vertices of 𝜟ABC are A(0, -5), B(-2, 1) and C(10, k). Find the value of
k if <ABC = 90.
Solution
Since <ABC = 90,
Gradient of AB × gradient of BC = -1
1−(−5) 𝑘−1
( )× ( ) = -1
−2−0 10−(−2)

𝑘−1
i.e. (-3)( )= -1
12
k–1=4
k=5
Type equation here. CHAPTER 6

SUMMARY
 The equation of a circle in the standard form is (x – a)2 + (y – b)2 = 𝑟 2 ,
where r > 0, (a, b) is the centre and r is the radius.
 The general formof the equation of a circle is 𝑥 2 +𝑦 2 +2gx +2fy +c = 0,
where 𝑔2 + 𝑓 2 - c > 0, (-g, -f) is the centre and √𝑔2 + 𝑓 2 − 𝑐 is the
 Graphs of the form y = 𝑎𝑥 𝑛 , where n is a rational number
(a) n is a positive rational number less than 1
1 1
(e.g. and )
2 3

3 5
(e.g. and )
2 3

1 3
(e.g. - and - )
2 2

 Graphs of the form 𝑦 2 = kx, where k is a real number

(a) k > 0

(b) k < 0
EXAMPLE
1. Find the centre and the radius of the circle 2𝑥 2 + 2𝑦 2 - 3x + 4y = -1.
Solution
Rewriting the equation, we have
2𝑥 2 + 2𝑦 2 - 3x + 4y + 1 = 0
3 1
i.e. 𝑥 2 + 𝑦 2 - 𝑥 + 2y + = 0
2 2

Comparing this with the general form of a circle 𝑥 2 + 𝑦 2 + 2gx+ 2fy+ c= 0

3 3
2g = − i.e. –g = ,
2 4
2f = 2 i.e. –f = -1,
3
Centre of circle = (-g, -f) = ( , -1)
4

Radius of circle = √𝑔2 + 𝑓 2 − 𝑐

3 1
=√(− )2 + (1)2 −
4 2
√17
=
4

2. In the figure, the line y = 6–x cuts the curve 𝑦 2 = 3x at the points A and B,
and the x-axis at C. Find
(i) The coordinates of A, B and C,
(ii) The ratio AC : CB.

Solution
(i) y= 6 –x (1)
2
𝑦 = 3𝑥 (2)
Subst. (1) into (2): (6 - x)2 = 3x
36 – 12x + 𝑥 2 = 3x
𝑥 2 – 15x + 36 = 0
(x-3)(x-12) = 0
x=3 or x=12
y=3 y= -6
A(3, 3) and B(12, -6)
Subst. y = 0 into (1) : x = 6
C(6, 0)
(ii) AC = √(3 − 6)2 + (3 - 0)2
= √18
3
= √2

CB =√(6 − 12)2 + (0 + 6)2

= √72
6
=√2
3 6
AC : CB = √2 : √2
=1:2